Efeito de escala em telhados verdes extensivos - Persch, Cristiano Gabriel (2019)
In the urban environment, where the permeable areas are gradually occupied by impermeable spaces, natural hydrological processes are also subject to changes. These impermeable surfaces promote the increase of the surface runoff and, with this, increase the frequency and intensity of the floods and inundations, reality of countless Brazilian cities. Among the alternatives pointed out to mitigate this problem, is the use of green roofs on buildings. Several studies relate their benefits, ranging from local to global. In addition to the reduction of surface runoff, green roofs have a proven effect in reducing heat islands, reducing energy consumption of buildings, promoting aesthetic improvement and increasing biodiversity in urban centers, for example. Therefore, the present study aimed to investigate experimentally the behavior of green roofs of different scales in the reduction of surface runoff over the period of one year. For this, four extensive green roofs (1m², 3m², 6m² and 12m²) were identically constructed, varying only one area. For these four roofs, monitoring was realized which allowed to determine the volumes of precipitation drained, the effectiveness in retention of the flow, the influence of precipitation characteristics on the hydrological response and the plant establishment. Compared to other roofs, the 12m² roof was more effective in retention and control of flow, evidencing the hypothesis that larger green roof scales produce a greater effect on the storage capacity of rainfall and, consequently, on the reduction and delay in generation of surface runoff. The largest roof had an average retention of 11mm / m², 11.5% higher than the 3m² roof retention, 18.5% higher than the 6m² roof, and 27.3% above the retention of the roof of 1m². In the same way, the green roof of larger area had the smaller peak flows and the greater delays in the generation of the flow. As for the precipitation characteristics, the one with the greatest influence on the retention and flow for the different scales was the precipitated volume; other factors, such as maximum volume precipitated in 1 hour and previous moisture of the substrate were also relevant and guiding the effectiveness of the roofs in the four scales analyzed. It was not possible to identify, during the monitoring period, the influence of the scale of the green roofs in the establishment and persistence of the vegetation, although there were differences in the amount of biomass and vigor of the plants throughout the different seasons. Thus, the results of the present study provide support for a better understanding of the effectiveness of the implantation of green roofs as a technique for the management of rainwater, and emphasize the importance of the scale of implantation of this type of technique, to increase its benefits in the control of the flow.